Synergic Inquiry (SI): An alternative framework for transformative learning. - Yongming Tang (Adult Education Research Conference, 1997)
This paper discusses SI which intends to help address a number of challenges facing transformative learning teachers and researchers. The SI framework is briefly introduced with the focus on how it creates contexts, processes and catalysts for transformative learning as well as its relationships with some existing learning theories.